2017
DOI: 10.1038/s41598-017-12667-y
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the alternative sigma factor RpoN to combat virulence in Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa is a Gram-negative, opportunistic pathogen that infects immunocompromised and cystic fibrosis patients. Treatment is difficult due to antibiotic resistance, and new antimicrobials are needed to treat infections. The alternative sigma factor 54 (σ54, RpoN), regulates many virulence-associated genes. Thus, we evaluated inhibition of virulence in P. aeruginosa by a designed peptide (RpoN molecular roadblock, RpoN*) which binds specifically to RpoN consensus promoters. We expected that RpoN*… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 65 publications
(83 reference statements)
5
37
0
Order By: Relevance
“…SCH0057-7, SCH0256-1, SCH0338-58, and SCH0354-1 were transformed with a plasmid expressing RpoN* or the empty vector and selected with gentamicin. If RpoN* affected transcription of virulence-related genes in different genetic backgrounds as previously reported (38), we expected attenuation of virulence-related phenotypes in P. aeruginosa CF patient isolates. RpoN* significantly reduced colony diameter in all four patient isolates in the swimming motility assay (Student’s t-test, ** p≤0.01, ***p≤0.0001) (Fig 4A).…”
Section: Resultssupporting
confidence: 57%
See 4 more Smart Citations
“…SCH0057-7, SCH0256-1, SCH0338-58, and SCH0354-1 were transformed with a plasmid expressing RpoN* or the empty vector and selected with gentamicin. If RpoN* affected transcription of virulence-related genes in different genetic backgrounds as previously reported (38), we expected attenuation of virulence-related phenotypes in P. aeruginosa CF patient isolates. RpoN* significantly reduced colony diameter in all four patient isolates in the swimming motility assay (Student’s t-test, ** p≤0.01, ***p≤0.0001) (Fig 4A).…”
Section: Resultssupporting
confidence: 57%
“…Antibiotic resistance is a problem in CF patients with P. aeruginosa infections (4749). We previously reported that RpoN* alters transcription of several genes involved in multidrug efflux pumps that confer natural resistance (38). Additionally, RpoN is implicated in tolerance to various classes of antibiotics (3436).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations